Визначення математичної логіки - Худаєва, С. А. (ХНУРЕ, 2020)
Symbolic logic is a section of formal logic in which logical inferences are explored through logical calculi based on a strict symbolic language. The mathematician is characterized by the widespread use of symbolism. Writing logical reasoning in the form of mathematical symbols gives the evidence a more concise, simple form. Formal logic operates with statements (our speech also consists of them
Keywords: філософія; визначення математичної логіки